Advances in Analysis and Design of Deep Foundations Proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017 on Sustainable Civil Infrastructures (Sustainable Civil Infrastructures, 2018)
This volume on "Advances in Analysis and Design of Deep Foundations" contains 22 technical papers which cover various aspects of analysis and design of deep foundations based on full-scale field testing, numerical modeling, and analytical solutions. The technical papers are 8-10 pages long that present the results and findings from research as well as practical-oriented studies on deep foundations that are of interest to civil/geotechnical engineering community. The topics cover a wide spectrum of applications that include evaluation of the axial and lateral capacity of piles, pile group effects, evaluation of the increase in pile capacity with time (or pile setup), influence of excavation on pile capacity, study the behavior of pile raft caisson foundations, evaluate the bearing capacity and settlement of piles from cone penetration tests, etc. This volume is part of the proceedings of the 1st GeoMEast International Congress and Exhibition on Sustainable Civil Infrastructures, Egypt 2017.